2014
DOI: 10.1136/bmjopen-2013-004711
|View full text |Cite
|
Sign up to set email alerts
|

Spatial inequalities in life expectancy within postindustrial regions of Europe: a cross-sectional observational study

Abstract: ObjectivesTo compare spatial inequalities in life expectancy (LE) in West Central Scotland (WCS) with nine other postindustrial European regions.DesignA cross-sectional observational study.SettingWCS and nine other postindustrial regions across Europe.ParticipantsData for WCS and nine other comparably deindustrialised European regions were analysed. Male and female LEs at birth were obtained or calculated for the mid-2000s for 160 districts within selected regions. Districts were stratified into two groups: sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
(50 reference statements)
2
14
0
1
Order By: Relevance
“…We projected that the elimination of socioeconomic differences between areas would increase survival by 7.1% and, even a slight reduction in socioeconomic differences would mean a 1.6% higher survival in these countries. Much has already been published about the effect of area-level of socioeconomic deprivation on life expectancy at birth and on overall mortality (Borrell et al 2014;Gotsens et al 2013;Hoffmann et al 2014;Mackenbach et al 2008;Mari-Dell'Olmo et al 2015;Richardson et al 2013;Taulbut et al 2014). In our study, we found that this effect exists later in life too.…”
Section: Discussionsupporting
confidence: 68%
“…We projected that the elimination of socioeconomic differences between areas would increase survival by 7.1% and, even a slight reduction in socioeconomic differences would mean a 1.6% higher survival in these countries. Much has already been published about the effect of area-level of socioeconomic deprivation on life expectancy at birth and on overall mortality (Borrell et al 2014;Gotsens et al 2013;Hoffmann et al 2014;Mackenbach et al 2008;Mari-Dell'Olmo et al 2015;Richardson et al 2013;Taulbut et al 2014). In our study, we found that this effect exists later in life too.…”
Section: Discussionsupporting
confidence: 68%
“…Post-industrial regions such as West Central Scotland, the France–Belgium border or Merseyside (UK, near Liverpool) have been characterised by high poverty levels and an erosion of social cohesion 33. Thanks to the use of a fine geographical scale, we were able to detect these areas, which remained among those with the lowest old-age survival over time.…”
Section: Discussionmentioning
confidence: 93%
“…The scale of this excess is considerable. It accounts for approximately 5,000 additional deaths per year in Scotland 17 , and makes a substantial contribution to the other principal mortality 'phenomena' associated with Scotland in recent times: the lowest, and most slowly improving, life expectancy in Western Europe; the widest mortality inequalities in Western Europe; and the persistently high rates of mortality among those of younger working ages 1,3,[20][21][22] . After adjustment for differences in deprivation, premature mortality (<65 years) in Scotland is 20% higher than in England & Wales (10% higher for deaths at all ages) 17 ; similarly, the excess for Glasgow compared with Liverpool, Manchester and Belfast has been shown to be approximately 30% for premature mortality, and around 15% for deaths at all ages 18,19 .…”
Section: Introductionmentioning
confidence: 99%